Khutbah Thariq bin Ziyad (Kajian Stilistika Arab) - Anisatu Thoyyibah (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2018)
Khutbah or khitabah is a form of prose literary that has its own characteristics in that it is presented. Even with the Khutbah carried by Thariq Ibn Ziyad too, which was said to give an influence on its audience, in this case is his soldiers. Through stylistics point of view, the writer studies Khutbah of Tariq Ibn Ziyad according to al-aswat (phonology), ikhtiyar al-lafz (Word preferences), and al-inhiraf (deviation) aspects. Based on this analysis it is found that there are elements of phonology, word's preferences, and deviations that relate to the events that occurred as said in the khutbah. Because of in fact that a work of literature cannot be separated from the historical frame of reference where the literary work is presented. Khutbah of Thariq Ibn Ziyad when it is seen from the stylistics indicate that this khutbah appears to provide stimulus, spirit, influence as well as reassuring to the soldiers who want to fight to the dhalim King, Roderick while expanding to a number of areas. This is proved by damir, harf, and mufradat used in the preaching that is very relevant to the conditions in those situations.